The Influence of Teacher Professional Competence on Education Quality Through Infrastructure as an Intervening Variable - Tri Mulyono Budi Hartanto; Nugroho Susanto; Nanda Saputra; Abdussyukur Abdussyukur; Ari Kartiko (Pascasarjana Pendidikan Agama Islam Institut KH. Abdul Chalim Mojokerto, 2022)
Professional competence and infrastructure are still classic problems that have not been entirely resolved. This study has the aim of analyzing infrastructure as an intervening variable (Y1). The exogenous variable (X1) is professional competence, and the endogenous variable (Y2) is education quality. This research method uses a type of quantitative research with explanatory research methods. The number of samples in this study was 140 people, who were selected using the census method. The results of the hypothesis test showed that teacher professional competence directly affects the quality of education, infrastructure directly affects the quality of education, and infrastructure can mediate the effect of teacher professional competence on education quality.